Analysis of the Need for English Learning Modules at SMA Negeri 4 Lubuklinggau - Sakiro, Yaumi; Supriyanto, Supriyanto; Sulistiyono, Sulistiyono (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study aims to analyze the needs in the development of a Predict, Observe, Explain (POE)-based teaching module, to improve conceptual understanding and learning interest in English subjects for students of SMA Negeri 4 Lubuklinggau, so a preliminary study is needed consisting of literature studies and field studies. The type of research conducted is qualitative descriptive research. The data collection instruments for this study are in the form of teacher needs analysis interview sheets and student needs analysis questionnaires. The learning media to be developed are in the form of POE-based English LKPD. Needs analysis was carried out to determine the teaching materials used by teachers, obstacles during learning and teaching materials needed by students. The results of the needs analysis of 32 students of SMA Negeri 4 Lubuklinggau obtained 100% have a handbook for learning English, however, 78.1% of students found the Procedure Text material in the Handbook difficult to understand. So according to students, the Handbook used is not sufficient as a learning resource and 84.4% of students need other teaching materials to support learning activities and 93.7% of students need other teaching materials that can improve high-level thinking skills. These results indicate the need to develop teaching materials in the form of POE-based LKPD for Procedure Text material.